2014
DOI: 10.1002/2013gl058840
|View full text |Cite
|
Sign up to set email alerts
|

Detecting super‐thin clouds with polarized sunlight

Abstract: We report a novel method for detecting cloud particles in the atmosphere. Solar radiation backscattered from clouds is studied with both satellite data and a radiative transfer model. A distinct feature is found in the angle of linear polarization of solar radiation that is backscattered from clouds. The dominant backscattered electric field from the clear-sky Earth-atmosphere system is nearly parallel to the Earth surface. However, when clouds are present, this electric field can rotate significantly away fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
35
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(38 citation statements)
references
References 26 publications
3
35
0
Order By: Relevance
“…Particularly, Fig. 10 shows that the AOLP from the ADRTM has a pattern in the neighborhood of the backward-reflecting angle that is very similar to those for clouds reported in Sun and Lukashin (2013) and Sun et al (2014Sun et al ( , 2015. This likely is because the refractive index for dust aerosols in our modeling is assumed to be 1.5 and the imaginary part is 0.…”
Section: Resultssupporting
confidence: 57%
“…Particularly, Fig. 10 shows that the AOLP from the ADRTM has a pattern in the neighborhood of the backward-reflecting angle that is very similar to those for clouds reported in Sun and Lukashin (2013) and Sun et al (2014Sun et al ( , 2015. This likely is because the refractive index for dust aerosols in our modeling is assumed to be 1.5 and the imaginary part is 0.…”
Section: Resultssupporting
confidence: 57%
“…As a complement to the work in Sun et al (2014), we further modeled the angle of linear polarization (AOLP) of reflected sunlight from clouds of different thermodynamic phases, particle shapes, and optical depth over oceans. In the modeling, the atmosphere, including the cloud and aerosol layers, is assumed to be plane-parallel.…”
Section: P -Polarization Feature Of Reflected Sunlight From Cloudsmentioning
confidence: 99%
“…In Sect. 2, modeling results supplementary to the work in Sun et al (2014) are reported for the polarization feature of reflected sunlight from clouds. The algorithm for retrieving the OD of super-thin clouds with polarized sunlight is introduced in Sect.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations